PENEGAKAN HUKUM BAGI CALON SATUAN PENGAMANAN TERKAIT SERTIFIKASI GADA PRATAMA DI PT. GLOBAL MUKTI MULYA ABADI - Indriyani, Ni Made Novi; Permadhi, Putu Lantika Oka (Jurnal Hukum Mahasiswa, 2024)
Security is a very substantial need for humans, both individually and in groups. Every day the media and news report acts of violence that threaten physical or psychological safety, so that humans place security as their basic need. Therefore, the author raises two problem formulations on how to legally regulate the obligation to have a Gada Pratama certificate for security unit candidates at PT. Global Mukti Mulya Abadi? What are the factors that influence law enforcement against prospective security guards? Research Method The research used in this research is sociological or empirical legal research, which is a study that views law as reality, including social reality, cultural reality and so on. Conclusion Legal Regulations Must Have a Gada Pratama Certificate for Security Unit Candidates at PT. Global Mukti Mulya Abadi is regulated in accordance with statutory regulations in Indonesia regulated in Article 3 paragraph 1 letter c of Law Number 2 of 2002 concerning Police as well as in the Republic of Indonesia State Police Regulation (hereinafter referred to as Perpol) Number 4 of 2020 concerning Security Swakarsa or Pam swakarsa. Factors that influence law enforcement against security guard candidates, namely the basic education policy (Diksar) in improving security unit skills is dominated by organization, in the implementation of basic education there are details of all training activities that must be carried out to achieve the objectives of basic security guard training and the procurement and development of a mechanism to coordinate the basic training of security guard members into an integrated and harmonious unit